The asymptotic dS swampland conjecture: a simplified derivation and a potential loophole - Hebecker, Arthur; Wrase, Timm (Fortschritte der Physik, 2019)
Recently, arguments for a refined de Sitter conjecture were put forward in [1]. Using the large distance conjecture of [2], the authors provide evidence for this dS conjecture in asymptotic regimes of field space, where the parametric control of string theory becomes arbitrarily good. Their main tool is Bousso's covariant entropy bound.[3] Here, we describe a simpler way to reach a similar conclusion. The argument is based on the fact that the cutoff of an effective theory with gravity decreases as the number of species grows. We then discuss a loophole in this argument and its possible counterpart in the assumptions underlying the entropy-based derivation. The idea is to consider potentials which, while they remain below an exponentially falling bound, have small oscillations leading locally to relatively flat regions or even to an infinite series of dS minima.